2017
DOI: 10.1007/978-3-319-62414-3_3
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Periconception Period: Immediate Effects in Cattle Breeding and in Assisted Reproduction Such as Artificial Insemination and Embryo Transfer

Abstract: In livestock breeding, the successful outcome is largely depending on the "periconception environment" which, in a narrow sense, refers to the genital tract, where gametogenesis and embryogenesis occur. During these early stages of development, gametes and embryos are known to be particularly sensitive to alterations in their microenvironment. However, as the microenvironment somehow reflects what is going on in the external world, we must widen our definition of "periconception environment" and refer to all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…In addition, underfed and overfed sheep had altered serum insulin, insulin-like growth factor-1, leptin, progesterone, and (or) estradiol concentrations, indicating they were affected metabolically as well [23,80]. Other studies reported decreased rates of fertilization with IVF and (or) decreased rates of early embryonic development in ewes or cows fed a low-(nutrient-restricted) or high-(ad libitum intake) energy diet during the periconceptual period [81][82][83][84][85]. Conversely, others have shown that an altered plane of nutrition during the periconceptual period had either positive or no effects on blastocyst formation and/or embryo health in sheep [83,86].…”
Section: Evidence For Programming By Maternal and Paternal Nutritionmentioning
confidence: 99%
“…In addition, underfed and overfed sheep had altered serum insulin, insulin-like growth factor-1, leptin, progesterone, and (or) estradiol concentrations, indicating they were affected metabolically as well [23,80]. Other studies reported decreased rates of fertilization with IVF and (or) decreased rates of early embryonic development in ewes or cows fed a low-(nutrient-restricted) or high-(ad libitum intake) energy diet during the periconceptual period [81][82][83][84][85]. Conversely, others have shown that an altered plane of nutrition during the periconceptual period had either positive or no effects on blastocyst formation and/or embryo health in sheep [83,86].…”
Section: Evidence For Programming By Maternal and Paternal Nutritionmentioning
confidence: 99%
“…The selection of cows for reproductive traits has contributed to the achievement of better reproductive rates in herds (Eetvelde et al 2017;Stangaferro et al 2018). The health of the cows, proper nutrition of animals, metabolic status, as well as environmental conditions has an impact on the reproductive success and health of the calves (Eetvelde et al 2017).…”
Section: The Influence Of the Housing System On Cow's Reproductionmentioning
confidence: 99%
“…Recent research presents that the use of assisted reproductive techniques may reduce the reproductive performance of dairy cattle (Figueiredo et al 2020). It had been proved that IVP embryos (in vitro embryo production) are characterized by darker cytoplasm due to the higher content of lipids, slower growth, and more frequent occurrence of apoptosis compared to in vivo embryos (Eetvelde et al 2017). Moreover, the use of these techniques exposes gametes and/or embryos to different environmental conditions than those in the female and male reproductive systems (Eetvelde et al 2017).…”
Section: The Influence Of the Housing System On Cow's Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many improvements made in the field of assisted reproduction, in vitro embryo production systems are still not as efficient as in vivo development (Rizos et al, 2017). Notwithstanding, it should be emphasized that gametes and embryos are exposed to spatial and temporal unnatural conditions during ART, whose consequences are not completely known (Van Eetvelde et al, 2017). In cattle, approximately 90% of oocytes cultured in vitro undergo nuclear and cytoplasmic maturation, from which 80% are fertilized and cleave at least once (Lonergan et al, 2003).…”
Section: Impact Of Assisted Reproduction On Embryo Development: Diffementioning
confidence: 99%